2021
DOI: 10.3390/ma14051193
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Propolis-Embedded Zeolite Nanocomposites for Implant Application

Abstract: This study investigates the potential of propolis-embedded zeolite nanocomposites for dental implant application. Propolis-embedded zeolite nanocomposites were fabricated by complexation of propolis and zeolites. Then, they were pelleted with Poly(L-lactide) (PLA)/poly(e-caprolactone) (PCL) polymer for the fabrication of a dental implant. The chemical properties of propolis were not changed during the fabrication of propolis-embedded zeolite nanocomposites in attenuated total reflection-fourier transform infra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…One of the main characteristics attributed to propolis in the literature is its antimicrobial action 13,15,25,29,30 . The oral environment is populated by a multi-species ecosystem.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…One of the main characteristics attributed to propolis in the literature is its antimicrobial action 13,15,25,29,30 . The oral environment is populated by a multi-species ecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…Among the engineering of mineralized dental tissues, the prolonged release of propolis over a month indicated that it can long-term inhibition of these dental pathogens in implants according to Son et al, 2021 25 . One of the compounds responsible for the antimicrobial action of propolis, cinnamic acid derivatives showed good stability in orally disintegrating lms over twelve weeks.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations